Older Women’s Situated Identities: Positioning Analysis Applied to Stories about Everyday Experiences Dealing With Physical Functional Changes - Kawabata, Makie; Narushima, Miya (Narrative Works, 2018)
Identities are not only constructed through coherent and unified stories about significant events but also formed within the interactions during everyday social encounters. Using positioning analysis, we explored how older women’s “small stories” from interviews can be used to identify their “situated selves” and how positioning analysis contributes to enhance our understandings about their experiences of physical functional changes. Positioning analysis helped us see how they continuously modify their positions to reconstruct their identities while they talk about everyday life. We should pay more attention to “small stories” about everyday activities as well as their coherent “big stories.”